Penerapan Cooperative Learning Berbasis Fellowship pada D.I Edutainment: Studi Kasus Gen Z - Tema Emiliana; Musafa Musafa (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the potential and challenges in implementing Fellowship-Based Cooperative Learning in D.I Edutainment, especially for Generation Z. The method used in this qualitative research is a case study, with data collection conducted through semi-structured interviews, participant observation, and documents. The unit includes the analysis of Gen Z participation, and involves facilitators, namely D.I Edutainment managers as informants. D.I Edutainment shows significant potential in implementing fellowship-based cooperative learning. Thanks to the interactive edutainment concept, small programs, and adequate human resource support. However, this study also identified challenges such as Generation Z's relatively short attention span, preference for digital media, variations in self-confidence levels, and the need for structure and motivation for ongoing collaboration. It is recommended that D.I Edutainment utilize, develop interactive and collaborative vehicles, train facilitators, design interesting project groups, and optimize community courage. From an academic perspective, further research is needed on the impact of cooperative learning, the role of technology, Generation Z's perceptions, and their social skills measurement models.